2001
DOI: 10.1002/micr.1026
|View full text |Cite
|
Sign up to set email alerts
|

Spleen autotransplantation in mice: A novel experimental model for immunology study

Abstract: The aim of the experimental model to develop a spleen transplant model in mice to study the role of spleen in autoimmune and transplant rejection. After a midline incision, splenectomy was performed. Four tiny segments were cut from the removed spleen and were rinsed at room temperature in physiological salt solution. The greater omentum was lifted and four omental pockets were created; four thin segments were then placed into the "nests," subsequently marked, and fixed using 8-0 suture. The abdomen was then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 8 publications
0
28
0
1
Order By: Relevance
“…The mouse model has certain advantages, including genetic homogeneity, which reduces individual differences, as well as decreased costs and fewer staffing requirements. 8,9 We previously reported that spleen autotransplantation restores most of the spleen's hematological and immunological functions. 9 As these studies were conducted 6 weeks after splenectomy and spleen transplantation, the long-term consequences of this procedure remain unknown.…”
Section: à9mentioning
confidence: 99%
“…The mouse model has certain advantages, including genetic homogeneity, which reduces individual differences, as well as decreased costs and fewer staffing requirements. 8,9 We previously reported that spleen autotransplantation restores most of the spleen's hematological and immunological functions. 9 As these studies were conducted 6 weeks after splenectomy and spleen transplantation, the long-term consequences of this procedure remain unknown.…”
Section: à9mentioning
confidence: 99%
“…3,12 In this study autogenous spleen grafts were prepared in the retroperitoneum and the results compared with those at sites more commonly used (IO and FPS). All animals that had undergone splenic autotransplantation had gross evidence of viable splenic implants ( Fig.…”
Section: Autogenous Splenic Implantsmentioning
confidence: 99%
“…9,10 Our study compared the multiple organ-chip model to a single liver, kidney, spleen, and intestine chip technique. The histological data revealed no difference: The spleen appeared to be the most preserved organ in our experimental model, as it had a recognizable structure without significant damage.…”
Section: Discussionmentioning
confidence: 99%